Historical Dynamics of the Boschbouw Area and Its Utilization in the Development of Madiun City - Rifo Ibnu Falah; Ikaputra Ikaputra (Interdisciplinary Social Studies, 2026)
The Boschbouw area is one of the heritage landscapes of forestry education from the Dutch East Indies colonial era, shaped by various historical dynamics of functions in Madiun City. Despite its historical value, the region has suffered from visual degradation, functional fragmentation, and loss of identity readability. This research aims to examine the historical dynamics, spatial character, visual quality, and potential for sustainable use of the area. The research method employs a mixed approach, drawing on primary sources from direct observation of four main aspects—ecology, economy and efficiency, equity and safety, as well as aesthetics—and secondary sources including document data, literature, and community perception questionnaires. The results of the analysis show that the area still retains its core elements, but the quality of the space has decreased due to development pressures, dysfunctional irregularities, and a lack of management integration. The analysis emphasizes that the area has strategic value for utilization, supported by historical attractions, creative economic potential, and high public acceptance. This study concludes that utilization should be directed toward strengthening regional identity to develop the Boschbouw area as an adaptive and sustainable landscape.